2016
DOI: 10.15639/teflinjournal.v27i1/82-100
|View full text |Cite
|
Sign up to set email alerts
|

using a Facebook Closed Group to improve Efl Students’ Writing

Abstract: <div class="page" title="Page 1"><div class="layoutArea"><div class="column"><p><span>This study investigates how social media, in this case Facebook, can be incorporated in ELT through e-dialogue journal writing shared in a Facebook closed group. Fifteen EFL students participated in this case study. They were second, third, and fourth year students of English Education Department of a university in Bandung, who voluntarily joined a Facebook closed group for about four months and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 22 publications
10
60
0
Order By: Relevance
“…The findings of the study (Rodliyah, 2016) did not describe the participants' contexts, nor did they show how the study sought to enhance students' experiences in those contexts. In the discussion section, the researcher constructs links between her own findings and other studies.…”
Section: Evaluating Research In Eltementioning
confidence: 80%
See 4 more Smart Citations
“…The findings of the study (Rodliyah, 2016) did not describe the participants' contexts, nor did they show how the study sought to enhance students' experiences in those contexts. In the discussion section, the researcher constructs links between her own findings and other studies.…”
Section: Evaluating Research In Eltementioning
confidence: 80%
“…For this purpose, the authors selected two research reports that showed to engage contrasting approaches to the concept of innovation and its relevance to students' learning. In the study by Rodliyah (2016), it is argued, the researcher attributes innovation value to an online communication platform, and its relevance to students' learning is described in terms that are not clearly linked to the concept of success. Arbitrary concepts are given positive value, with no framework being offered to validate this assessment.…”
Section: Framework For Designing and Evaluating Education Researchmentioning
confidence: 99%
See 3 more Smart Citations